Serious Adverse Events Cluster in Participants Experiencing the Primary Composite Cardiovascular Endpoint: A Post Hoc Analysis of the SPRINT Trial. (13th January 2020) - Botchway, Albert; Buhnerkempe, Michael G; Prakash, Vivek; Al-Akchar, Mohammad; Adekola, Bemi; Flack, John M
Abstract: BACKGROUND: Intensively treated participants in the SPRINT study experienced fewer primary cardiovascular composite study endpoints (CVD events) and lower mortality, although 38% of participants experienced a serious adverse event (SAE). The relationship of SAEs with CVD events is unknown. METHODS: CVD events were defined as either myocardial infarction, acute coronary syndrome, decompensated heart failure, stroke, or death from cardiovascular causes. Cox models were utilized to understand the occurrence of SAEs with CVD events according to baseline atherosclerotic cardiovascular disease (ASCVD) risk. RESULTS: SAEs occurred in 96% of those experiencing a CVD event but only in 34% ( P < 0.001) of those not experiencing a CVD event. Occurrence of SAEs monotonically increased across the range of baseline ASCVD risk being approximately twice as great in the highest compared with the lowest risk category. SAE occurrence was strongly associated with ASCVD risk but was similar within risk groups across treatment arms. In adjusted Cox models, experiencing a CVD event was the strongest predictor of SAEs in all risk groups. By the end of year 1, the hazard ratios for the low, middle, and high ASCVD risk tertiles, and baseline clinical CVD group were 2.56 (95% CI = 1.39–4.71); 2.52 (1.63–3.89); 3.61 (2.79–4.68); 1.86 (1.37–2.54), respectively—a trend observed in subsequent years until study end. Intensive treatment independently predicted SAEs only in the second ASVCD risk tertile. CONCLUSIONS: The occurrence of SAEs is multifactorial and mostly related to prerandomization patient characteristics, most prominently ASCVD risk, which, in turn, relates to in-study CVD events.